Profiling of Bacterial Species from Covid-19 Faecal Samples in Kurdistan Region-Iraq - Hama-Ali, Mohammed A.; Hasan, Ayad H. (Science Journal of University of Zakho, 2023)
The invasion of intestinal cells by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) may have an impact on the gut bacteria. This study investigated the alteration of gut bacteria during SARS-CoV-2 viral infection and after recovery. Faecal samples were collected from ten RT-PCR-conﬁrmed COVID-19 patients and five healthy participants (served as a control group) from November 21st, 2021 to April 1st, 2022. The faeces samples were collected three times, at the time of infection, after seven days of the infection and on day fifty after clearance of SARS-CoV-2. Serum samples were used to perform serological tests for the control group and COVID-19 survived patients. Pure culture techniques and classical and molecular approaches were used to isolate and identify the bacterial population in the collected faeces. The faecal bacterial communities of patients with COVID-19, those who recovered, and the five healthy people were compared. Significant alteration in culturable gut bacteria was observed in COVID-19 patients compared to the control group. This alteration was expressed by the existence of four bacterial species, which were Escherichia fergusonii, Citrobacter portucalensis, Comamonas kerstersii, and Shigella flexneri. In addition, two respiratory tract-associated bacterial pathogens, Klebsiella pneumoniae and Klebsiella aerogenes were recovered from the faecal samples of 40% of COVID-19 patients. The results even revealed that Staphylococcus aureus was more prevalent in faeces samples from those with SARS-CoV-2 infections than the healthy individuals. Faecal analysis of COVID-19 patients showed the existence and elevation of pathogenic bacteria in the large intestine in comparison to the healthy group. Further studies are required to highlight how an alteration of gut microbiomes affects the course of COVID-19 infection.
Keywords: Gut microbiota; COVID-19; 16s RNA gene; SARS-CoV-2; Comamonas kerstersii